Prohibition of interest and gambling in the Islamic economic system: اسلامی معاشی نظام میں سود اور قمار کی حرمت و ممانعت - Yousufi, Waqar; Ghazi, Dr. Shahnaz (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
The Prophet admonished riba (usury) in its all methods in his farewell Pilgrimage speech. The article examines the rules of interest (usury) and Maysir (gambling) and how it fits within the realm of Islamic finance , as it is described in the Holy Qur’an and as it is demonstrated by the Prophet in his Sunnah . Following verses of the Qur’an and its interpretations through the hadiths of Prophet are also described in the article. Referring to an argument saying the modernists claim that what is prohibited in Qur’an is the form of interest (usury) and Maysir (gambling) mentioned to the then prevailing practice of lending in the pre-Islamic era, the authors confidently ruled out the logic saying that any increase over and above the principal should be riba (usury) and Maysir (gambling) and as such it is prohibited. The modernists also raised some controversial issues like-‘difference between riba (usury) and maysir (gambling) ‘individual and institutional riba’. All these titles are defeated with satisfactory Shari`ah references. While answering the issues specified earlier, the authors categorically explored the inborn beauties of Islamic Banking and finance as well as disclosed the differences between Islamic and Conventional economy system. The authors, in a nut shell, stress on the point in this paper that any form of riba and maysir is strictly avoided in the Islamic society and Islamic economy System.